Arnold O. Beckman and William Hewlett - Robert A. Isaacs Photography (1985)
Dr. Beckman and Dr. Hewlett, co-founder of Hewlett-Packard, converse at dinner preceding Stanford Symposium that marked Beckman's 50th Anniversary. According to a caption on the back of this photograph, Hewlett, speaking "as a competitor," saluted Beckman Instruments as "an absolutely remarkable organization," and Dr. Beckman as "one of the really great entrepreneurs in this country."
Keywords: Beckman, Arnold O.; Hewlett-Packard Company; Hewlett, William R.